PENGARUH PENERAPAN ICE BREAKING ONLINE (IBO) DI ERA PANDEMI COVID-19 PADA PESERTA DIDIK MATA PELAJARAN DASAR-DASAR BUDIDAYA PERIKANAN DI SMK NEGERI 9 MAKASSAR - Muamalia, Mutmainnah; Yanto, Subari (Jurnal Biogenerasi, 2024)
This research is classroom action research which aims to determine the effect of applying Ice Breaking Online (IBO) on Learning Motivation, Interest in Learning, and Learning Outcomes in Students at SMK Negeri 9 Makassar. Research data was obtained from questionnaire results, interview data, and learning tests from students. The results of research on the effect of improving student learning in cycle I were 74%, cycle II 16%. The final results of the study showed that the first cycle was 79% and the second cycle was 91%. Analysis using the normality gain test for cycle I was 0.69% and cycle II was 0.90%. It can be concluded that the application of Ice Breaking Online (IBO) can improve learning outcomes for students, both motivation, interest and learning outcomes for students for the basics of fisheries cultivation at SMKN 9 Makassar.